2018
DOI: 10.12669/pjms.344.15521
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Teaching Obstetrics and Gynaecological Procedural Skills on Patients versus Models: A randomized trial

Abstract: Objective:To compare the effectiveness of learning procedural skills on patients versus mannequins and models.Methods:Seventy four interns from two consecutive batches at the Department of Obstetrics and Gynaecolgy Unit-I at Jinnah Postgraduate Medical Center Karachi participated in the study between April and September 2014. Five basic skills; taking a cervical (Pap) smear, intrauterine contraceptive device insertion, manual vacuum aspiration, making/ suturing an episiotomy and active management of the third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…No comparative study was conducted for the efficiency, effectiveness and acceptability of the virtual reality in medical. No study explained the adaptability of routine use of simulation environment 18…”
Section: Introductionmentioning
confidence: 99%
“…No comparative study was conducted for the efficiency, effectiveness and acceptability of the virtual reality in medical. No study explained the adaptability of routine use of simulation environment 18…”
Section: Introductionmentioning
confidence: 99%
“…The students strongly felt that newer teaching methodologies should replace conventional classroom lectures. A recent randomized trial [15] compared the efficacy of two teaching strategies on skill learning in medical students during internship and concluded that training is better if done on mannequins prior to patients. Similar experiences had been reported by first-year nursing students who had undergone highfidelity simulation learning in Japan [16].…”
Section: Discussionmentioning
confidence: 99%
“…3 Evidence specifically from Obstetrics and Gynecology, a field with unique barriers to trainee exposure and practice, suggests that trainees who use simulation training models to practice gynecological procedural skills can develop similar competencies compared with in-person training and can be used as an initiation platform for teaching infrequently performed procedures. 4 Using newer technology such as telemedicine in simulationbased training presents a feasible solution in the pandemic era. Traditional telemedicine approaches, such as recorded videos and live teleconferencing, have limited utility in procedural and surgical applications, providing little opportunity to interact and supervise the trainee during the activity.…”
mentioning
confidence: 99%
“…There is increasing evidence to suggest that simulation-based training in health care improves patient outcomes 3 . Evidence specifically from Obstetrics and Gynecology, a field with unique barriers to trainee exposure and practice, suggests that trainees who use simulation training models to practice gynecological procedural skills can develop similar competencies compared with in-person training and can be used as an initiation platform for teaching infrequently performed procedures 4 …”
mentioning
confidence: 99%